Identidade visual e sua relação com a linguagem não verbal - Silva, João Carlos Riccó Plácido da [UNESP]; Paschoarelli, Luis Carlos [UNESP]; Raposo, Daniel; Menezes, Marizilda Santos (My University, 2012)
The visual identity is based on a semantic relationship of several signs that make up a coherent system. A bimédia language formed by text and image complement to create an understandable message. This study aims the use of non-verbal communication in the corporate visual identity design project, contextualizing the role of the designer as mediator for informational corporate message to their audiences.

A identidade visual assenta numa relação semântica de diversos signos que integram um sistema coerente. Uma linguagem bimédia de texto e imagem que se complementam de modo a criar uma mensagem compreensível. Este estudo visa o uso da linguagem não verbal no âmbito do projeto de identidade visual corporativa, contextualizando o papel do designer informacional enquanto mediador da mensagem corporativa para os seus públicos.
Keywords: Design; Visual identity; Nonverbal language; Design; Identidade visual; linguagem não verbal